Cardiovascular outcomes and safety with linagliptin, a dipeptidyl peptidase‐4 inhibitor, compared with the sulphonylurea glimepiride in older people with type 2 diabetes: A subgroup analysis of the randomized CAROLINA trial. Issue 2 (6th December 2020) - Espeland, Mark A.; Pratley, Richard E.; Rosenstock, Julio; Kadowaki, Takashi; Seino, Yutaka; Zinman, Bernard; Marx, Nikolaus; McGuire, Darren K.; Andersen, Knut Robert; Mattheus, Michaela; Keller, Annett; Weber, Maria; et al.
Abstract: Aim: To compare the cardiovascular (CV) safety of linagliptin with glimepiride in older and younger participants in the CAROLINA trial in both prespecified and post hoc analyses. Materials and Methods: People aged 40 to 85 years with relatively early type 2 diabetes, inadequate glycaemic control and elevated CV risk were randomly assigned to linagliptin 5 mg or glimepiride 1 to 4 mg. The primary endpoint was time to first occurrence of three‐point major adverse CV events (MACE: CV death, non‐fatal myocardial infarction, or non‐fatal stroke). We evaluated clinical and safety outcomes across age groups. Results: Of 6033 participants, 50.7% were aged <65 years, 35.3% were aged 65 to 74 years, and 14.0% were aged ≥75 years. During the 6.3‐year median follow‐up, CV/mortality outcomes did not differ between linagliptin and glimepiride overall (hazard ratio [HR] for three‐point MACE 0.98, 95.47% confidence interval [CI] 0.84, 1.14) or across age groups (interaction P >0.05). Between treatment groups, reductions in glycated haemoglobin were comparable across age groups but moderate‐to‐severe hypoglycaemia was markedly reduced with linagliptin (HR 0.18, 95% CI 0.15, 0.21) with no differences among age groups ( P = 0.23). Mean weight was −1.54 kg (95% CI –1.80, –1.28) lower for linagliptin versus glimepiride. Adverse events increased with age, but were generally balanced between treatment groups. Significantly fewer falls or fractures occurred with linagliptin. Conclusions: Linagliptin and glimepiride were comparable for CV/mortality outcomes across age groups. Linagliptin had significantly lower risk of hypoglycaemia and falls or fractures than glimepiride, including in "older‐old" individuals for whom these are particularly important treatment considerations.